2020
DOI: 10.21894/jopr.2020.0057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulphuric Acid Concentration on the Physico-Chemical Properties of Microfibrillated Cellulose From Oil Palm Empty Fruit Bunch Fibre

Abstract: The interest for microfibrillated cellulose (MFC) has been present within the academic sector since the 1980s, but recently this material has become commercially available as it is growing significantly in the industrial sector. Therefore, in this study the oil palm empty fruit bunch fibre was selected to be synthesised into MFC. This study focused on the effect of acid concentrations on the isolation of MFC from oil palm empty fruit bunch fibre (OPEFB-fibre) using the acid hydrolysis method, followed by ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The morphology of MCC showed that the diameter size of MCC decreased along with the length of the fibres as the concentration of sulphuric acid rose. Before treatment, OPEFBs' raw fibres are composed up of bundles bound together by lignin and hemicellulose, and their surface morphology is uneven and rough [21]. Due to the depolymerization of cellulose polymers, a shorter chained MCC was produced, which had a different structure from that of cellulose [22].…”
Section: Sem Analysis Of MCCmentioning
confidence: 99%
“…The morphology of MCC showed that the diameter size of MCC decreased along with the length of the fibres as the concentration of sulphuric acid rose. Before treatment, OPEFBs' raw fibres are composed up of bundles bound together by lignin and hemicellulose, and their surface morphology is uneven and rough [21]. Due to the depolymerization of cellulose polymers, a shorter chained MCC was produced, which had a different structure from that of cellulose [22].…”
Section: Sem Analysis Of MCCmentioning
confidence: 99%
“…Many studies have been conducted to sustainably utilize biomass wastes from the oil palm industry. Among these studies, the use of OPEFB in the pulp and paper industry to replace the existing paper from wood sources was explored (Ibrahim 2003;Tanaka et al 2004).…”
Section: Oil Palm Empty Fruit Bunch (Opefb) Fibermentioning
confidence: 99%
“…Near infrared spectrometry (NIRS) is one of the nondestructive methods (Ismail, 2010), consisting of light detection and ranging (LiDAR) scanning systems that have been studied to classify oil palm ripeness in the Malaysian oil palm industry, where the proposed approach was based on calculating the reflectance percentage using the concept of linearity (Zulkifli et al, 2018). Another application classified oil palm ripening into under-ripe, ripe and over-ripe categories using hand-held, multi-parameter fluorescence sensors and blue-green (447 nm) and far-red (685 nm) wavelengths.…”
Section: Introductionmentioning
confidence: 99%